PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP KINERJA KEBERLANJUTAN - Muhammad Rizky Arjunanda; Rafrini Amyulianthy (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2026)
This study aims to analyze the effect of firm characteristics, namely profitability, leverage, and firm size, on sustainability performance. Profitability is measured using Return on Assets (ROA), leverage is measured using the Debt to Equity Ratio (DER), and firm size is measured using the natural logarithm of market capitalization (LnMarket Capitalization). This study employs a quantitative approach using secondary data. The research sample consists of 44 companies listed on the Indonesia Stock Exchange (IDX) and included in ESG Ratings/ESG Scores, selected through purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS version 22. The results indicate that profitability and firm size have a positive and significant effect on sustainability performance, while leverage has a negative and significant effect on sustainability performance. These findings suggest that financial capacity and firm scale support the implementation of sustainability activities, whereas high leverage may limit a company’s ability to allocate resources to improve sustainability performance. This study is expected to provide insights for companies, investors, and other stakeholders in understanding the factors that influence corporate sustainability performance.